Analisa Medical Transaction Untuk Mengetahui Berbagai Penyakit Pada Masyarakat - Saifullah, Faris, Dedi Gunawan, S.T., M.Sc (2016)
Drugstore is one of service facilities in the medical field on the community. During this time a lot of the drugstore already take advantage from data transaction but many also has not been able to take advantage of data transaction and was only be data not worthless. Therefore, the research data mining transaction done to take advantage of the data. The study was conducted in "Apotek Asahi Farma" Gondang, District Sragen. The data mining techniques in this research is using Apriori algorithm that applied in an application. Focus thinking of this research is how to use data mining concept to find frequent itemsets by Apriori algorithm and create a useful system to know disease of community in around drugstore. Frequency item sets will processed by database and then will be analyze to get result of information disease in the society. This is the disease has attack the society on July, 1 through 7 2015 is Rheumatoid Athritis, Osteo Athritis and Gout. By using data transaction can be obtained information a variety of the disease that according with threshold, dated early data and the end data that was inclusion can be known users directly without having to do survey.